2020
DOI: 10.1177/1069397120910982
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting the Scientific Wealth of Nations

Abstract: It has been repeatedly demonstrated that economic affluence is one of the main predictors of the scientific wealth of nations. Yet, the link is not as straightforward as is often presented. First, only a limited set of relatively affluent countries is usually studied. Second, there are differences between equally rich countries in their scientific success. The main aim of the present study is to find out which factors can enhance or suppress the effect of the economic wealth of countries on their scientific su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 90 publications
2
33
0
Order By: Relevance
“…Although a typical bibliometric analysis prefers to focus on variables that are related to articles, authors, references, and citations (e.g., Xie et al, 2019), there is convincing evidence from many studies that both the quantity and quality of countries' research output are significantly influenced, not just by economic, but also social and cultural factors (Harzing & Giroud, 2014;Leydesdorff & Wagner, 2009;Mueller, 2016;Schofer, 2004;Tahamtan, Afshar, & Ahamdzadeh, 2016). The Worldwide Governance Indicators (WGI), for instance, which was developed by the World Bank to characterize practices and institutions through which authority is exercised in a country (Kaufmann, Kraay, & Mastruzzi, 2010), has been found to be an influential factor in driving scientific excellence (Jüri Allik, Lauk, & Realo, 2020;Gantman, 2012).…”
Section: Predominantlymentioning
confidence: 99%
See 1 more Smart Citation
“…Although a typical bibliometric analysis prefers to focus on variables that are related to articles, authors, references, and citations (e.g., Xie et al, 2019), there is convincing evidence from many studies that both the quantity and quality of countries' research output are significantly influenced, not just by economic, but also social and cultural factors (Harzing & Giroud, 2014;Leydesdorff & Wagner, 2009;Mueller, 2016;Schofer, 2004;Tahamtan, Afshar, & Ahamdzadeh, 2016). The Worldwide Governance Indicators (WGI), for instance, which was developed by the World Bank to characterize practices and institutions through which authority is exercised in a country (Kaufmann, Kraay, & Mastruzzi, 2010), has been found to be an influential factor in driving scientific excellence (Jüri Allik, Lauk, & Realo, 2020;Gantman, 2012).…”
Section: Predominantlymentioning
confidence: 99%
“…In accordance with this general development, Allik and colleagues (J. Allik, 2013;Jüri Allik et al, 2020) proposed the High Quality Science Index (HQSI), which combines the mean citation rate per paper with the percentage of papers that has reached the top 1% level of citations in a given research area and an age cohort of published papers. Interestingly, they discovered that significant correlations between the HQSI and economic indicators-Gross National Income (GNI) and expenditure on research and development (GERD)-became insignificant when the indicator of good governance -WGI-was taken into account (Jüri Allik et al, 2020). Good governance, to explain very briefly, is when authority is transparently and responsibly exercised, government has the capacity to effectively formulate and implement sound policies, and when citizens are respected and social institutions are accountable to people, not to any one privileged group (Kaufmann et al, 2010).…”
Section: Predominantlymentioning
confidence: 99%
“…Although it appears to be true that the top of the citation distribution is a more informative characteristic of the scientific impact than indicators based on average values (van Leeuwen et al, 2003), the selectivity of databases unwillingly eliminates "losers" whose counting would have decreased the mean citation rate. Thus, the scientific impact of nations can be increased not only by the number of highly cited papers but also by neglecting those papers that could jeopardize the mean citation rate (Allik et al, 2020a). To improve citation indicators, a new measure-INSI-was proposed, which, in addition to the citation statistics, takes also into account the number of research areas in which a country/territory was successful to enter the ESI.…”
Section: Discussionmentioning
confidence: 99%
“…These and other similar problems caused a shift in the bibliometric research from impact scores based on average values of citations toward the use of indicators that reflect the top of the citation distribution, such as the number of papers reaching the highest rank of citations (van Leeuwen et al, 2003). In accordance with this general trend, a composite index-the High Quality Science Index (HQSI; Allik, 2013;Allik et al, 2020a)-was proposed characterizing nations by combining the mean citation rate per paper with the percentage of the papers that have reached the top 1% level of citations in a given research area and an age cohort of published papers. Although the average values of citations and the top of the citation distribution are highly correlated, typically r = 0.80 or higher (Allik, 2013), combining these two indicators into a composite index allowed to compensate some minor discrepancies between the two indicators.…”
Section: The Scientific Impact Derived From the Disciplinary Profilesmentioning
confidence: 99%
“…In personality psychology, especially North America and Central Europe are dominant forces, while the salience and impact of researchers from other countries (e.g., from South America, Africa, Asia, and Oceania) still seem to lag behind. Although the reasons for such "nation gaps" may be varied (e.g., Allik et al, 2020;Harzing & Giroud, 2014;Thelwall & Levitt, 2018), the lack of diversity in researchers could be detrimental to the field of personality science. For example, an empirical study from Hofstra et al (2020) on ~1.2 million US doctoral recipients (1977-2015) indicated that higher rates of innovation and novelty could be expected specifically from demographically underrepresented and minority groups, though their contributions seemed to have been less impactful and discounted more.…”
Section: Expanding Diversities In the Fieldmentioning
confidence: 99%